Characterization of polymeric thermal expander - Chua, Chi Ann (2016)
This report presents the material properties of a silicone resin, Silres H62 C. The experiments were carried out in several ways including compression tests, DMA (Dynamic Mechanical Analysis) and TMA (Thermo Mechanical Analysis). The material Silres H62 C were configured in both non-constrained and constrained forms under the same curing condition, 200°C for 21hours. According to the experimental results from TMA, the non-constrained linear coefficient of thermal expansion (CTE) of Silres H62 C is about 220ppm/°C at the temperature range from 100°C to 180°C.The constrained CTE of Silres H62 C is about 650ppm/°C temperature range from 100°C to 180°C. The Young’s modulus obtained from compression test is 250MPa whereas the storage modulus obtained from single cantilever test (DMA) is 650MPa. The maximum thermal stress of constrained Silres H62 C occurs at 60°C for both static and dynamic condition. The maximum thermal stress is 8MPa at 10Hz frequency and 4MPa at static condition.